Spatiotemporal spatfall dynamics and prevailing estuarine conditions for optimal oyster (Crassostrea tulipa) spat availability in selected Gulf of Guinea brackish systems - Chuku, Ernest Obeng; Yankson, Kobina; Obodai, Edward Adzesiwor; Acheampong, Emmanuel; Aheto, Denis Worlanyo (Frontiers in Marine Science, 2023)
The precariousness of wild harvests of spat and adult oysters resulting from oceanographic oscillations renders its fishery and aquaculture fragile at localities where data on the stocks and hatchery technology are sparse. Predicting the periods and locations of available seed oysters in estuaries are necessary preconditions for selecting sites for oyster aquaculture in emerging oyster aquaculture industries. By deploying artificial spat collectors affixed to bamboo racks, spatfall (spat/m2) of the mangrove oyster Crassostrea tulipa (Lamarck, 1819) was assessed in four tropical coastal intertidal systems along the Gulf of Guinea coast, specifically Ghana, to guide seed procurement for aquaculture and inform its management. Significant spatiotemporal variations in spatfall were found among and within the brackish systems. The spatfall regimes were unique in each ecosystem albeit with an overall preponderance of dry season availability of spat. Locations with reef oysters had superior spatfall to mangrove root-adapted-oyster areas. Narkwa, a relatively small lagoon with reef oysters had the highest annual mean spatfall, which was 1.3, 2.5, and 9.8 folds the spatfall in Densu Delta, Benya Lagoon and Whin Estuary, respectively. Spatfall varied significantly by depth as the more frequently exposed top collectors harvested lesser spat than submerged collectors. There was a year-round availability of spat, confirming continuous spawning in C. tulipa. Spatfall was significantly marked by fluctuations in prevailing dissolved oxygen and salinity from a multilinear regression model including other factors such as temperature, turbidity and pH. Prevailing dissolved oxygen and salinity levels in the estuaries for optimal spat settlement were 1.68 – 3.40 mg L-1 and 11.00 – 29.33 ppt (parts per thousand), respectively. The findings of this study are recommended as scientifically informed reference points for the sustainable seed procurement for aquaculture production and management of the C. tulipa fishery in the region.